Sex differences in secondary school achievement – The contribution of self-perceived abilities and fear of failure. (April 2015) - Wach, F.-Sophie; Spengler, Marion; Gottschling, Juliana; Spinath, Frank M.
Abstract: While previous studies demonstrated the existence of a 'gender gap', according to which girls outperform boys in their scholastic achievement, the reason for these differences is yet unclear. We used structural equation analyses and multiple-group comparisons to determine sex-specific influences of self-reported motivational variables (domain-specific self-perceived abilities, fear of failure) on teacher-reported mid-term school grades of 140 boys ( M age  = 10.9) and 185 girls ( M age  = 10.8) from Germany. Our results suggest that the gender gap derives at least partly from sex differences in the contribution of these motivational variables to children's performance in school: Regarding German, girls' level of self-perceived abilities was higher and also more relevant for their performance. Moreover, higher levels of fear of failure led to worse Math grades only for girls, suggesting the presence of gender-stereotypic beliefs. Further research should investigate the impact of additional constructs, e.g., gender-stereotype awareness, self-regulation. Highlights: Study on sex differences in school achievement at the beginning of secondary school. Self-perceived abilities predicted boys' and girls' school achievement. The impact of self-perceived abilities on German grade was stronger for girls. Fear of failure predicted only the girls' Math grade. Differentiation between subjects is crucial to examine sex differences adequately.